IMF Staff Papers, Volume 47, No. 3. (IMF Staff Papers; IMF Staff Papers ;, 2001)
This paper provides an overview of the recent theoretical and empirical research on herd behavior in financial markets. It looks at what precisely is meant by herding, the causes of herd behavior, the success of existing studies in identifying the phenomenon, and the effect that herding has on financial markets. The paper also surveys a selected number of studies that evaluated the demand for money using the error-correction model approach in the 1990s across a range of industrial and developing countries.